2016
DOI: 10.1016/j.jamcollsurg.2015.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Validation of the National Field Triage Guidelines for Identifying Seriously Injured Persons

Abstract: BACKGROUND-The national field trauma triage guidelines have been widely implemented in US trauma systems, but never prospectively validated. We sought to prospectively validate the guidelines, as applied by out-of-hospital providers, for identifying high-risk trauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
90
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(96 citation statements)
references
References 34 publications
3
90
0
Order By: Relevance
“…This study demonstrated that, although field triage sensitivity for identifying patients with serious injuries (Injury Severity Score 17 [ISS] ≥16; range, 0-75, with higher numbers indicating greater injury severity) appeared to be better in rural vs urban regions (81% vs 65.8%), only 12.5% of seriously injured rural patients were initially transported to major trauma centers and only 39.3% were ultimately cared for in major trauma centers. 16 However, the primary results of this study did not allow a detailed assessment of rural vs urban differences in trauma care.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…This study demonstrated that, although field triage sensitivity for identifying patients with serious injuries (Injury Severity Score 17 [ISS] ≥16; range, 0-75, with higher numbers indicating greater injury severity) appeared to be better in rural vs urban regions (81% vs 65.8%), only 12.5% of seriously injured rural patients were initially transported to major trauma centers and only 39.3% were ultimately cared for in major trauma centers. 16 However, the primary results of this study did not allow a detailed assessment of rural vs urban differences in trauma care.…”
mentioning
confidence: 90%
“…We conducted a preplanned secondary analysis of the prospective injury cohort of that study 16 to detail rural vs urban differences in field triage, processes of trauma care, injury severity, and mortality. We sought to use these data as an opportunity to address ongoing questions about differences in process and outcomes between urban and rural trauma patients.…”
mentioning
confidence: 99%
“…Because some research has demonstrated higher estimates for under-triage than used for this study, 10,11 unbiased prospectively-derived values for under- and over-triage would further inform the cost models and may shift the cost-effectiveness results. We also assumed that EMS transport patterns based on triage status would remain the same under different triage strategies, though it is possible that these patterns would shift based on the perceived accuracy (or lack thereof) of “new” triage guidelines.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, over-triage (1 – specificity) represents the proportion of patients without serious injuries transported to major trauma hospitals, a measure of resource waste and excess cost (national target ≤ 35% 6 ). Research suggests that under-triage is as high as 34% 7-11 and approximately 50% among older adults. 7,10-12 Revisions to the national guidelines have sought to reduce under-triage without increasing over-triage, 2 although under- and over-triage are inversely related.…”
Section: Introductionmentioning
confidence: 99%
“…An auto-calculated mREMS score would provide pre-hospital personnel and providers the ability to quickly and accurately understand the patient severity and the predicted risk of mortality. The score can help trauma patients be quickly triaged to the appropriate healthcare facility, based upon objective criteria, instead of the loosely utilized CDC field triage guidelines, which have been shown as insensitive in its ability to identify seriously injured patients [21]. With a statistically proven trauma score driving the triage of trauma patients, the CDC field triage guidelines could be supplemented or perhaps replaced with an objective algorithm, such as the mREMS score, to increase the likelihood that patients are taken to the most appropriate trauma facility.…”
Section: Discussionmentioning
confidence: 99%